USURY AND BANK INTEREST IN THE CONCEPT OF MOHAMMAD HATTA AND SYAFI’I ANTONIO - Abdul Mufid (Jurnal Ilmiah Pesantren, 2023)
Interest is the amount of money paid or for the use of capital obtained by the Bank from the Customer. This amount, for example, is expressed by one level or percentage of capital related to it which is called capital. Bank interest is still causing controversy among scholars and other Muslim figures. Therefore, this study examines the legal basis and background of the differences in thoughts of Mohammad Hatta and Syafi’i Antonio in determining the legal status of usury and bank interest. This study is a literature study of the books by Muhammad Hatta and Syafi’i Antonio on Riba and Bank Interest as primary sources, and books written by other authors about it. To analyze the collected data, analytical descriptive method is used.The results showed that according to Mohammad Hatta, bank interest was not haram, even though the interest rate was predetermined, what was forbidden was the bank interest contained in consumer loans because it was very detrimental. Meanwhile, productive loans do not contain elements of oppression and extortion. Meanwhile, Syafi’i Antonio firmly stated that bank interest is the same as riba which is forbidden and anything related to usury is haram. Syafi’i Antonio concluded that if you want to avoid interest, you should use Islamic banking services. In Islamic banking there is no interest system, but instead uses a profit sharing system that is mutually beneficial to both parties, so that there is no element of oppression and extortion